Structural steel design to BS 5950 part 1 - Joannides, Frixos (Thomas Telford, 2002)
BS5950 - the design code for structural steel - has been greatly revised. Joannides and Weller introduce the new code and provide the necessary information for design engineers to implement the code when designing steel structures in the UK.
Keywords: Steel, Structural -- Design.; elektronické knihy; electronic books